HYDRAULIC OPERATIONAL SIZING OF A FACULTATIVE LAGOON SEWAGE TREATMENT PLANT: A CASE STUDY FOR THE CITY OF FORMOSO DO ARAGUAIA – TO. (REMUNOM, 2024)
With population growth, especially in the last twenty years, there has been a significant increase in water consumption by the population and industries. Despite greater investment in sanitation, a large proportion of the water used still does not receive adequate treatment before being discharged into water bodies. This article will demonstrate the sizing of a sewage treatment plant for the municipality of Formoso do Araguaia – Tocantins.